Organizational Prestige, Employee Engagement and Employee Retention in Selected Deposit Money Banks in Delta State, Nigeria - NWAFILI, Asinedu Kennedy; Ijoyah, Christopher Tuni (PT Keberlanjutan Strategis Indonesia, 2026)
This study investigated the effect of organizational prestige and employee engagement on employee retention in selected deposit money banks in Delta State, Nigeria. Cross-sectional survey design was employed, collecting data from a sample of 370 bankers using structured questionnaire. This study involved 10 deposit money banks with a population of 9,743, and using the Krejcie and Morgan table of sample size determination, a sample size of 370 respondents was drawn. Both descriptive and inferential statistical analytical tools were used in data analysis. Descriptive analysis was performed on the respondents’ biographic data while multiple regression and correlation analysis were carried out on the research hypotheses. Findings revealed that organizational prestige (β = 0.883, t = 39.152, P = 0.000 < 0.05) and employee engagement (β = 0.115, t = 5.106, P = 0.000 < 0.05) are positively significant to employee retention among deposit money bank employees in Delta State, Nigeria. It was concluded that organizational prestige and employees’ engagement improve staff retention in deposit money banks in Delta State, Nigeria.